NAC Family Transcription Factors in Tobacco and Their Potential Role in Regulating Leaf Senescence - Li, Wei; Li, Xiaoxu; Chao, Jiangtao; Zhang, Zenglin; Wang, Weifeng; Guo, Yongfeng (Frontiers in Plant Science, 2018)
The NAC family is one of the largest families of plant-specific transcription factors and NAC proteins play important regulatory roles in a variety of developmental and stress response processes in plants. Members of the NAC family transcription factors have been shown to be important regulators of leaf senescence in a number of plant species. Here we report the identification of the NAC family in tobacco (Nicotiana tabacum) and characterization of the potential role of some of the tobacco NAC transcription factors in regulating leaf senescence. A total of 154 NAC genes (NtNACs) were identified and clustered together with the Arabidopsis NAC family into fifteen groups (a-o). Transcriptome data analysis followed qRT-PCR validation showed that the majority of the senescence-up-regulated NtNACs fall into subgroups NAC-b and f. A number of known senescence regulators from Arabidopsis also belong to these two subgroups. Among these senescence-up-regulated NtNACs, NtNAC080, a close homolog of AtNAP, is a positive regulator of leaf senescence. Overexpression of NtNAC080 caused early senescence in Arabidopsis leaves and NtNAC080 mutation induced by Cas9/gRNA in tobacco led to delayed leaf senescence.